Immune and cytokine/chemokine responses of PBMCs in rotavirus‐infected rhesus infants and their significance in viral pathogenesis. Issue 8 (1st April 2019) - Zhou, Yan; Qiao, Hongtu; Yin, Na; Chen, Linlin; Xie, Yuping; Wu, Jinyuan; Du, Jing; Lin, Xiaochen; Wang, Yi; Liu, Yang; Yi, Shan; Zhang, Guangming; et al.
Abstract: The rotavirus (RV) is the most important causative agent of severe gastroenteritis in infants and children aged less than 5 years worldwide. However, the response and the roles of peripheral blood mononuclear cell (PBMC) in RV clearance have yet to be fully elucidated. In this study, we established the neonatal rhesus monkey model of RV infection with histopathological changes in the small intestine. Then, we investigated gene expression changes in PBMCs from the monkey model of RV infection. Similar pathways regulated in rhesus monkeys that received intragastric administration of the RV monkey SA11 strain (G3P[2]) and the human wild‐type strain ZTR‐68 (G1P[8]). Gene profiling showed differences in functional genes mainly associated with chemokine signaling pathways and cytokine‐cytokine receptor interactions post RV infection. Transferrin and C‐C motif chemokine ligand 23 (CCL23) gene expression were upregulated in PBMCs of monkeys when stimulated by simian and human RV strains. Monkeys infected with RV had an enhanced and prolonged inflammatory response that was associated with increased levels of CCL20, CCL23, and C‐X‐C motif chemokine ligand 1; while inhibition of major histocompatibility complex class I expression may be important for immune evasion by RV. The RV infection was also characterized by pathological changes in the small intestine with a cytokine and chemokine storm. This study identified the chemokine signaling pathway and immune response genes involved in RV infection in infant rhesus monkeys. The SA11 RV strain is more suitable for establishing a monkey diarrhea model than the ZTR‐68 RV strain. Highlights: Infant rhesus monkeys can be used as an animal model to study the interaction between the RV and host as well as the pathological mechanisms. After both SA11 and ZTR‐68 strain RV infection in infant rhesus monkeys, most of the differential genes mainly dealing with 'immune response' and 'inflammatory reaction'. The chemokine signaling pathway and cytokine‐cytokine receptor interaction maybe involved in RV infection in infant rhesus monkeys. Monkeys infected with RV had an enhanced and prolonged inflammatory reaction response to RV (simian SA11 and human ZTR‐68) that was associated with increased levels of type I IFN, IL‐6, IL‐4, CCL20, CCL23 and CXCL‐1.